Pengaruh Kualitas Pelayanan dan Harga Terhadap Kepuasan Pelanggan di Industri Restoran - Nasution, Sri Wanti (Journal of Trends Economics and Accounting Research, 2024)
The aim of this research is to find out and analyze the various factors that influence customer satisfaction. In this research, researchers carried out a quantitative associative approach. Associative research is research that aims to determine the influence or relationship between two or more variables. Data analysis is statistical in nature with the aim of testing research hypotheses that have been applied previously. The population in this research is all consumers with a sample of 20 consumers taken randomly. The data collection technique in this research is by using a questionnaire. The data analysis technique used is to carry out multiple linear regression analysis. In this research, the multiple linear regression analysis method uses SPSS 22 software. The results of this research are that service quality has a significant effect on customer satisfaction. Price influences consumer satisfaction. Meanwhile, service quality and price together influence customer satisfaction. It can be seen that the calculated t value for the service quality variable (X1) is 2.337 > t table 2.093 and the significant value is 0.005 < 0.05, so ha is accepted and ho is rejected. Meanwhile, t calculated for the price variable (X2) with a calculated t value = 2.612 > t table = 2.093. So the decision is that Ha is accepted and Ho is rejected.